War crimes and genocide investigations in Latvia - Jansons, Ritvars (Genocidas ir rezistencija, 2025)
Following Latvia’s regained independence, investigations into war crimes and genocide began in 1992. At the end of the 1990s, issues related to the events of the occupation period became politically sensitive in Latvia. The country felt that the processes of that period, including the crimes committed and the genocide, were not just historical issues. These events are still impacting public opinion today. Issues related to the Second World War have a particular impact on Latvia’s relations with other countries and its aspirations to join NATO and the EU. On 13 November 1998, the President of the Republic of Latvia established the Commission of Historians, which publishes books and organises conferences. The Commission works in four groups, which study: 1) the repression of civilians by the Soviet government in 1940–1941; 2) the Holocaust; 3) the German occupation of Latvia in 1941–1945; 4) the problems of Stalin’s regime in Latvia in 1945–1956. The Commission of Historians has organised conferences on the above-mentioned topics and published books.
Keywords: Latvia; genocide; war crimes; legislations